Social isolation impairs active avoidance performance and decreases neurogenesis in the dorsomedial telencephalon of rainbow trout - Ausas, María Soledad (2019)
Alterations in the social environment, such as isolating an individual that would normally live in a social group, can generate physiological responses that compromise an individual's capacity to learn. To investigate this, we tested whether social isolation impairs learning skills in the rainbow trout. We show that rainbow trout can achieve an active avoidance (AA) learning program with inter-individual variability. Moreover, c-Fos expression in dorsomedial telencephalon (Dm) correlates with the AA performance, indicating that this structure is involved in this cognitive task. Given that Dm participates in AA learning and this region is under plastic remodelling by addition of new-born neurons, we tested whether social isolation impinges on adult neurogenesis and, consequently, on the Dm cognitive outcome. Trout were reared for four weeks in control or isolated conditions. We found that social isolation diminished the percentage of adult-born neurons that are being incorporated into Dm network. Interestingly, the same isolation treatment also induced a severe deficit in the AA performance. Our results demonstrate a structure-to-function relationship between the Dm and the learning ability in an AA task, indicate that social isolation reduces the incorporation of adult-born neurons into Dm, and show that social isolation impairs the Dm-related cognitive function.